Library: An Evolving Entity / Roziya Abu and Mary Carroll - Abu, Roziya; Carroll, Mary (Universiti Teknologi MARA, Kedah, 2018)
In the breach on information technological innovativeness, a library has become a more dynamic informative institution. Library’s collection development has become more diversified and less physical, and the public library’s roles and functions are now extended to not just the storage and gathering of information and knowledge, but also to interacting, communicating and socializing. In many countries around the world, the contemporary public library stands as a community hub. It has become an engaging, inspiring and informative citizen’s centre. Hence it helps to build strong and empowered communities. The purpose of this paper is to discuss the initiatives of development activities and programs that underpin libraries and public libraries in supporting their local community development.